2021
DOI: 10.1002/arch.21844
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin A2 induces apoptosis in three cell lines derived from the fall armyworm, Spodoptera frugiperda

Abstract: Animals maintain homeostasis of cell numbers, constantly creating new cells and eliminating others. Programmed cell death, apoptosis, is a mechanism of cell elimination and it acts in many aspects of animal biology. Drawing on the biomedical background, several signals launch the apoptosis mechanisms, including prostaglandins (PGs). Based on this information, we posed the hypothesis that PGs similarly induce apoptosis in insect cell lines. We used three Spodoptera frugiperda cell lines, including two newly est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…While it has recently been found that prostaglandin A2 induces apoptosis in three cell lines derived from Spodoptera frugiperda ( Wang et al, 2021 ), there remains a general need for further studies on the influence of eicosanoids on the process of apoptosis in insects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it has recently been found that prostaglandin A2 induces apoptosis in three cell lines derived from Spodoptera frugiperda ( Wang et al, 2021 ), there remains a general need for further studies on the influence of eicosanoids on the process of apoptosis in insects.…”
Section: Discussionmentioning
confidence: 99%
“…Two primary programmed cell death signaling pathways are known: apoptosis and autophagy. Both are evolutionarily conserved and can be induced by a range of endogenous and exogenous factors, including the levels of toxins, hormones, growth factors, nitric oxide and cytokines, as well as by heat, irradiation, nutrient deprivation, infection, hypoxia and increased intracellular calcium concentration ( Elmore, 2007 ; Kazek et al, 2020 ; Cao et al, 2021 ; Nury et al, 2021 ; Wang et al, 2021 ). In addition, the apoptotic pathway has characteristic morphological changes and biochemical processes, including cytoplasmic and nuclear condensation, phosphatidylserine extrusion, vacuolization, chromatin condensation and DNA fragmentation; in addition, a number of apoptotic bodies are formed that are ultimately engulfed by surrounding cells ( D’Arcy, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is an essential biological process for insects as it is recognized and accepted as a distinctive and important mode of programmed cell death (Y. Wang et al, 2021; Y. Zhang et al, 2016). More importantly, apoptosis is critically important in the development of the nervous system (Wnuk & Kajta, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis is an essential biological process for insects as it is recognized and accepted as a distinctive and important mode of programmed cell death (Y. Wang et al, 2021;Y. Zhang et al, 2016).…”
Section: Effect Of Ncb On Aw1 Cell Apoptosismentioning
confidence: 99%
“…Programmed cell death is directly related to the cells death in bioreactor, being 2 mechanisms of death can be observed; apoptosis and autophagy. The programed cell death (apoptosis) mechanism is activated by various external and internal factors as heat, irradiation nutrient depletion, shear stress, hypoxia, toxin accumulation, as well as a cell response to viral infections, (Kazek et al, 2020; Cao et al, 2021; Nury et al, 2021; Wang et al, 2021; Wrońska et al 2022, Mendonça et al 2008; Arden et al 2007; Mendonça et al 2002; Meneses-Acosta et al 2001;). These factor act directly on the membrane of cells or on mitochondria (Bedoui et al, 2020), being acting on a caspase activation cascade (Bock and Tait, 2020; Kesavardhana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%